"The New World". Musica e narratività nel cinema di Terrence Malick - Francesco Finocchiaro (Musica Docta, 2011)
The New World (USA, 2005) is the fourth full-length film’s title of the American director Terrence Malick. The movie tells the legendary love story between Princess Pocahontas (Q’orianka Kilcher) of the Powathan tribe and the English soldier and explorer John Smith (Colin Farrell). The background of the historical events concerns the foundation of one of the first European settlements in the New World, at the close beginning of 17th Century. The specific topic of the proposed didactical unit, which is addressed to a 2nd or 3rd class of the Secondary School, consists in the analysis of some film sequences, that all employ the main theme of the second movement (Adagio) from the Wolfgang Amadeus Mozart’s Piano Concerto K 488. The didactic unit is based on an audiovisual analysis, that focuses on developing some categories, concepts and tools, which can enrich the reading strategies of a kind of text – the syncretic cinematographic one – with a central role in the contemporary music production and consumption. Malick’s work not only represents a polished example of music employment in a movie, but also deals with a topic of a relevant historical importance, that is the encounter between the Old and New World; indeed this topic is particularly suitable for encouraging a reflection upon cultural diversity and interethnic communication.